RNAi Reveals Role of Insulin-Like Androgenic Gland Hormone 2 (IAG2) in Sexual Differentiation and Growth in Hermaphrodite Shrimp - Liu, Fang; Shi, Wenyuan; Ye, Haihui; Liu, An; Zhu, Zhihuang (Frontiers in Marine Science, 2021)
Insulin-like androgenic gland hormone (IAG) is the most widely known hormone that regulates sexual differentiation in crustaceans. Previously, a transcriptome study described two transcripts of IAGs (Lvit-IAG1 and Lvit-IAG2) in the peppermint shrimp Lysmata vittata, a species characterized by a rare reproductive system of protandric simultaneous hermaphroditism (PSH). Herein, we explored the function of Lvit-IAG2 via RNA interference (RNAi) experiments, and then compared the functional differences between the two IAGs. We demonstrated that Lvit-IAG2 positively regulated the expression of crustacean hyperglycemic hormone (Lvit-CHH) in eyestalk ganglion but exhibited no significant effect on the expression of gonad-inhibiting hormone (Lvit-GIHs) and crustacean female sex hormone (Lvit-CFSHs). Besides, Lvit-IAG2 gene knockdown caused degeneration in appendices masculinae (AM) and suppressed germ cells at the secondary spermatocyte stage. Moreover, silencing the Lvit-IAG2 gene impeded ovarian development, including smaller previtellogenic oocytes, and lower expression of vitellogenin (Lvit-Vg) gene in hepatopancreas and vitellogenin receptor (Lvit-VgR) gene in the ovarian region. Notably, silencing the Lvit-IAG2 gene impeded individual growth of the species. Collectively, findings from this study demonstrate that Lvit-IAG2 and Lvit-IAG1 coordinatively function to modulate sexual differentiation in L. vittata; meanwhile, Lvit-IAG2 stimulates the growth of the PSH species.